Effects of music on recreational runners' performance and subjective experiences during and after running - Chua, Khai Leng (2015)
The purpose of this study was to examine the effects of music on recreational runners’ performance and subjective experiences during and after a 30 minutes run. Previous research reported that music yields several benefits on running when compared to the control condition. This study hypothesized that music improves runners’ performance and provides more positive experience during and after the run when compared to control. In this study, a group of 20 healthy undergraduate students from Nanyang Technological University (10 male, 10 female; M age = 23.6 years, SD = 1.57; M body mass index = 21.4 kg/m2, SD = 1.89) were randomly selected and assigned to control and music condition. They performed a 30 minutes run on treadmill at moderate intensity over 2 trials. Findings showed significant difference in rate of perceived exertion (p = .024), feeling scores (p = <.001) and felt arousal scores (p = <.001) during the 30 minutes run. Furthermore, the scores of subject vitality (p = .026), perceived performance (p = .001), interest/enjoyment (p = .021) and perceived competence (p = <.001) in the music condition were significantly better than those in the control condition. In conclusion, runners’ ran significantly further and elicited more positive experience during and after running in the music condition when compared to the control condition.